Alpha-tocopherol enhances spermatogonial stem cell proliferation and restores mouse spermatogenesis by up-regulating BMI1 - Peng, Mei; Wu, Jintao; Wang, Weifan; Liao, Tianlong; Xu, Simeng; Xiao, Di; He, Zuping; Yang, Xiaoping (Frontiers in Nutrition, 2023)
Purpose: Spermatogonial stem cells (SSCs) are essential for maintaining reproductive function in males. B-lymphoma Mo-MLV insertion region 1 (BMI1) is a vital transcription repressor that regulates cell proliferation and differentiation. However, little is known about the role of BMI1 in mediating the fate of mammalian SSCs and in male reproduction. This study investigated whether BMI1 is essential for male reproduction and the role of alpha-tocopherol (α-tocopherol), a protective agent for male fertility, as a modulator of BMI1 both in vitro and in vivo. Methods: Methyl thiazolyl tetrazolium (MTT) and 5-ethynyl-2’-deoxyuridine (EDU) assays were used to assess the effect of BMI1 on the proliferative ability of the mouse SSC line C18-4. Real-time polymerase chain reaction (PCR), western blotting, and immunofluorescence were applied to investigate changes in the mRNA and protein expression levels of BMI1. Male mice were used to investigate the effect of α-tocopherol and a BMI1 inhibitor on reproduction-associated functionality in vivo. Results: Analysis revealed that BMI1 was expressed at high levels in testicular tissues and spermatogonia in mice. The silencing of BMI1 inhibited the proliferation of SSCs and DNA synthesis and enhanced the levels of γ-H2AX. α-tocopherol enhanced the proliferation and DNA synthesis of C18-4 cells, and increased the levels of BMI1. Notably, α-tocopherol rescued the inhibition of cell proliferation and DNA damage in C18-4 cells caused by the silencing of BMI1. Furthermore, α-tocopherol restored sperm count (Ctrl vs PTC-209, p=0.0034; Ctrl vs PTC-209+α-tocopherol, p=0.7293) and normalized sperm malformation such as broken heads, irregular heads, lost and curled tails in vivo, as demonstrated by its antagonism with the BMI1 inhibitor PTC-209. Conclusion: Analysis demonstrated that α-tocopherol is a potent in vitro and in vivo modulator of BMI1, a transcription factor that plays an important role in in SSC proliferation and spermatogenesis. Our findings identify a new target and strategy for treating male infertility that deserves further pre-clinical investigation.